Microarray-based analysis reveals a novel role of the miRNA-613/SNAI2/CXCR4 axis in atrial fibrillation - Zhenyu Zhai; Yiligong Qi; Longlong Hu; Zumao Gan (PLoS ONE, 2025)
Backgrounds Atrial fibrillation (AF) can lead to substantial morbidity and mortality in clinic. The previous studies demonstrated that miRNAs were closely associated with several cardiovascular diseases, however, the role of miRNAs in the pathogenesis of AF has not been fully elucidated. In order to investigate the important role of miRNA in the mechanisms of AF, we conducted the study through bioinformatics analysis. Methods We downloaded the miRNA expression profile (GSE68475) and mRNA expression profile (GSE31821) from the Gene Expression Omnibus (GEO) database to explore the differentially expressed miRNAs and mRNAs. The criteria for significant differentially expressed miRNA and mRNA using the R limma package were: adjusted P-value < 0.05, log2fold-change ≥ 1. The target mRNAs related to differentially expressed miRNAs of AF were predicted by using Functional enrichment analysis tool. We Screened overlapped mRNAs based on differentially expressed mRNAs and miRNA related mRNAs using Draw Venn Diagram. GO enrichment analysis and KEGG pathway analysis were conducted to explore the role of miRNAs and mRNAs in the pathogenesis of AF. Results A total of 70 differentially expressed miRNAs were screened including 33 up-regulated miRNAs and 34 downregulated miRNAs. All of 94 differentially expressed mRNAs were screened including 56 up-regulated mRNAs and 38 downregulated mRNAs. There were three co-expressed up-regulated differentially expressed genes, including CXCR4, SNAI2, and FHL1. We showed the results of GO functional enrichment analysis and KEGG pathway analysis ranked by enrichment score (-log P value) respectively. Conclusion Compared with patients of normal sinus rhythm, miRNA-613 was significantly down-regulated in patients with AF. We demonstrated that SNAI2 and CXCR4 may target genes of miRNA-613 for the first time. Our findings may provide new ideas for clarifying the molecular mechanism of atrial fibrillation.